Understanding hazard perception in filmed and simulated environments - Runham, Patrick (2016)
Each year millions of people around the world are killed or injured due to being involved in collisions while driving on the roads, with young and inexperienced drivers most likely to be killed or injured. Numerous studies have found a link between the likelihood of a driver being involved in a collision and their hazard perception (HP) ability, with young and inexperienced drivers having inferior HP abilities compared to older and more experienced drivers. This thesis presents a series of studies that investigate the factors that affect HP performance as well as comparing different HP testing methods. The traditional video-based method is explored as well as new methods utilising a high-fidelity driving simulator (used as an analogue of real-world driving) in order to see if there are ways of making HP testing more representative of detecting and responding to hazards while driving on the road. This thesis also explores the use of functional near-infrared spectroscopy (fNIR) as a portable and flexible means of measuring dorsolateral prefrontal cortex (DLPFC) activity during driving. Comparisons between video-based HP testing (similar to that used in the UK HP test) and simulator-based HP testing revealed significant differences in psychophysiological and behavioural responses, indicating that video-based methods may not be representative of HP while driving on the road. fNIR was found to primarily measure task workload and to be a reliable means of recording DLPFC activity across a range of different driving tasks. The fNIR results also demonstrated that DLPFC was similar when performing a simulator-based HP test and a hybrid simulator method using simulation replays, suggesting that introducing elements of driving simulation may help bridge the gap between current video-based HP testing methods and HP while driving on the road. These findings have important implications for the theoretical and practical aspects of HP testing and the use of fNIR in driving research.